Evaluation of efficacy 3Dimensional 4-hole trapezoid condyle plate for treatment of base of condyle fracture - Paul, Roger; Suvvada, Bharathi; Polomarasetty, Prasanna; Thumu, Sai kumar; Santosh, P. V. (National journal of maxillofacial surgery, 2022)
The aim of our study was to evaluate the effectiveness of open reduction and internal fixation of the base of condyle using a 3D 4-hole trapezoid condyle plate (4-HTCP). A group of 25 subjects of an age range of 21-52 years (mean 32.7 ± 8.7 years) were treated of which, 7(28%) were female and 18 (72%), were male. All the patients were examined according to standard protocol. A retromandibular approach was used in all the patients. The time taken for operating on the condyle alone was recorded it was between 30 minutes to one hour in 5 (20%) patients, between one-two hours in 19 (76%) patients and greater than two hours in 1 (4%) patient. Time taken from reduction of fracture to placement of the last screw was recorded. In 15 (60%) patients the time taken was less than ten minutes, in 10 (40%) patients the time taken ranged from 10-15 minutes. 6 (24%) patients needed additional exposure to facilitate the procedure. Postoperatively all the patients were followed up for a minimum of 9 months and a maximum of 30 months (mean 19.5 ± 5.87 months). The range of mandibular movements was satisfactory. The maximum incisal opening was in the range of 25-37 mm (mean- 31.4 ± 3.38 mm)on the first post-operative day. 31.4 ± 3.4 mm 6 weeks postoperatively, 43.8 ± 4.3 mm 3 months postoperatively, 46.7 ± 2.9 mm 6 months postoperatively and 49.7 ± 4.5 mm 9 months postoperatively. Taking into consideration the transient hypofunction of the facial nerve (8%) and TMJ disorder (8%) the aggregate complication rate in our study was 16%. Our study concludes that 4HTCP is a reliable and rigid choice of osteosynthesis for the base of condyle fractures.